Covalent organic-inorganic polyoxometalate hybrids in catalysis - Iftikhar, Tuba; Rosnes, Mali H. (Frontiers in Chemistry, 2024)
Polyoxometalates (POMs) are a class of compounds known for the vast range of tunable structures and properties available, leading to applications in areas such as catalysis, energy, and advanced medicine. The ability to covalently functionalize POMs with organic components has been investigated extensively to tune the physical and chemical properties of the resulting hybrid materials. These hybrids, where the organic entity is covalently attached to the POM-core (Class II hybrid POMs) result in a vast library of promising customizable catalytic systems, displaying tunable properties with a high level of synergy between the polyanion and the organic component. A number of Class II hybrids have been investigated for a wide range of catalytic applications, and here, we give a brief overview of Class II hybrids of the p-block elements and their applications in catalysis.